2(x-3)+3=13

Simple and best practice solution for 2(x-3)+3=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)+3=13 equation:


Simplifying
2(x + -3) + 3 = 13

Reorder the terms:
2(-3 + x) + 3 = 13
(-3 * 2 + x * 2) + 3 = 13
(-6 + 2x) + 3 = 13

Reorder the terms:
-6 + 3 + 2x = 13

Combine like terms: -6 + 3 = -3
-3 + 2x = 13

Solving
-3 + 2x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 2x = 13 + 3

Combine like terms: -3 + 3 = 0
0 + 2x = 13 + 3
2x = 13 + 3

Combine like terms: 13 + 3 = 16
2x = 16

Divide each side by '2'.
x = 8

Simplifying
x = 8

See similar equations:

| x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x | | -6.8(7.9+1.2*-7.3)+3.7=4.2*-7.3+40.90016 | | 1/8+2/3= | | 1/3+2/3= | | 5y+11=6 | | -6.8(7.9+1.2x)+3.7=4.2x+40.90016 | | x^2-1x+40=0 | | (m+2n+1)(m-n+2)=5 | | x^2+12x+35x=0 | | 4x+13=-29-2 | | x+2x+6x+18x=160 | | 7(x*5)=9(6+4) | | 4m^2+4x=60 | | 3(2p-1)=8 | | -4x^2+24x-63=0 | | -2x^2-10x+14=0 | | 3(4x-7)=-33 | | 2xsquare+15y-13=0 | | -x^2-7= | | (-5)-(-11)=x | | (-5)-(-11)= | | 9xsquared=324 | | 4x-3=7+2 |

Equations solver categories